2018
DOI: 10.1007/s13205-018-1487-5
|View full text |Cite
|
Sign up to set email alerts
|

Primer design and amplification efficiencies are crucial for reliability of quantitative PCR studies of caffeine biosynthetic N-methyltransferases in coffee

Abstract: Primers having suboptimal amplification efficiencies were shown to falsely represent fold change expression of the N-methyltransferases gene family involved in caffeine biosynthesis in Coffea canephora. To study this phenomenon, the role of stability of the internal reference gene, as well as the amplification efficiency correction of the primers was investigated. GAPDH and Ubiquitin exhibited a good stability for studying the ontogeny of endosperm tissue, as well as the leaf transcriptome during stress from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Other experimental conditions can impact qPCR reactions and subsequent analyses, including primer design [32], template quality [25], enzymes (DNA polymerase types and conditions) [33], other reaction components [24], cycling conditions [34], sample handling and pipetting errors, reference genes for normalization [35], and others. Jointly, these parameters will be considered as part of further assays using bacterial models in a more biological context, including the quantification of determinants that we have previously found in the perturbome [17], the SOS response [36], or the response to ciprofloxacin [18] in P. aeruginosa AG1.…”
Section: Discussionmentioning
confidence: 99%
“…Other experimental conditions can impact qPCR reactions and subsequent analyses, including primer design [32], template quality [25], enzymes (DNA polymerase types and conditions) [33], other reaction components [24], cycling conditions [34], sample handling and pipetting errors, reference genes for normalization [35], and others. Jointly, these parameters will be considered as part of further assays using bacterial models in a more biological context, including the quantification of determinants that we have previously found in the perturbome [17], the SOS response [36], or the response to ciprofloxacin [18] in P. aeruginosa AG1.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to exogenous miRNA, appropriate reference genes are needed to normalize extracted endogenous miRNA levels, and reference gene selection must be prioritized because some reference genes can differ depending on the sample condition and type. With normalization, the evaluation of amplification efficiency is also crucial for the reliability of qRT-PCR studies [ 37 , 73 , 74 ]. Sreedharan et al demonstrated improvements in the reliability of expression data through primer-dependent improvements in amplification efficiency [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…With normalization, the evaluation of amplification efficiency is also crucial for the reliability of qRT-PCR studies [ 37 , 73 , 74 ]. Sreedharan et al demonstrated improvements in the reliability of expression data through primer-dependent improvements in amplification efficiency [ 73 ]. Variations in primer concentration and annealing temperature, as well as primer design, can affect amplification efficiency and consequently affect the reliability of expression data.…”
Section: Discussionmentioning
confidence: 99%
“…The primers were designed using the PrimerBlast tool 59 , with a final product size of approximately 150 base pairs (Supplementary Table S1 ). The primer efficiency was calculated by using the formula: E = 10 (-1/slope) 60 . The thermal cycling conditions for qRT-PCR was: 95 °C for 5 min, then 40 cycles of 94 °C for 15 s, 55 °C for 30 s and 72 °C for 30 s, and a final melting curve step from 65 °C to 95 °C with a ramp speed of 0.5 °C per 5 s. Actin, a housekeeping gene, was used as an internal control 61 (F: 5′-GGAGAAGCTCGCTTACGTG-3′ & R: 5′-GGGCACCTGAACCTTTCTGAA-3′).…”
Section: Methodsmentioning
confidence: 99%